Scents for Serpentes: are familiar humans un-hiss-takable? - Vonk, Jennifer; Jordan, Amity; Pappas, Jacob; Stellman, Koi; Leibowitz, David (Frontiers in Ethology, 2025)
IntroductionAlthough snakes are commonly housed in captivity, little research has investigated the impacts of common stimuli in their environments. Familiar scents, for example, may be indicative of threat or the lack thereof and may be associated with stress. Snakes have a highly developed sense of smell and can discriminate prey, mates, and kin by scent. Humans are regularly present in captive environments, but only one study has tested whether a single snake species discriminated scents of familiar and unfamiliar humans.MethodsWe investigated whether 19 snakes of nine species housed privately or at nature centers showed differential behavioral responses to the scents of familiar human handlers, unfamiliar humans, and control stimuli.ResultsThere were no significant effects of condition, housing, or sociality on movement, investigation, or tongue-flicking rates.DiscussionWe did not replicate a previous finding with corn snakes, likely due to procedural or housing differences, which will be important for future explorations of this understudied topic.